The maze a labyrinthine compendium - Hyland, Angus 1963-; Wilson, Kendra (Laurence King Publishing, 2018)
"Mazes have been a part of civilization for at least 4,000 years, and there are more being built now than ever before. What is it about these magical life-size puzzles that continues to intrigue us? This beautifully illustrated book will delight lovers of mazes, acting as a guide, directory and puzzle book combined. Specially commissioned illustrations by Thibaud Hérem represent 60 real and imagined mazes from around the world, with a bird's eye view of each maze so that readers can make their own journey. Each maze is also accompanied by a fascinating and witty short history"--Publisher's description
Keywords: Labyrinth; Maze gardens; Labyrinths; Maze puzzles / History; Maze puzzles; History